Depression: A Modifiable Risk Factor for Poor Outcomes in Fibromyalgia. (August 2022) - Munipalli, Bala; Allman, Madeleine E.; Chauhan, Mohit; Niazi, Shehzad K.; Rivera, Fernando; Abril, Andy; Wang, Benjamin; Wieczorek, Mikolaj A.; Hodge, David O.; Knight, Dacre; Perlman, Adam; Abu Dabrh, Abd Moain; et al.
Background: About 4 out of 10 fibromyalgia patients suffer from depression. The European Alliance of Associations for Rheumatology (EULAR) guidelines recommend using antidepressants to treat fibromyalgia. Objective: To determine predictors of improved outcomes following a multicomponent treatment program. Design: We designed this longitudinal treatment outcome study to evaluate the prevalence of depression symptoms in patients diagnosed with fibromyalgia at a tertiary care facility, and the impact of depression on functional outcomes after completing a multicomponent fibromyalgia treatment program. Setting: Tertiary care center. Patients: This study included 411 adult patients with fibromyalgia who completed a multicomponent treatment program for fibromyalgia. Expert physicians performed comprehensive evaluations following American College of Rheumatology (ACR) criteria to confirm fibromyalgia before referral to the program. Intervention: An intensive outpatient multicomponent treatment program consisting of 16 hours of cognitive behavioral strategies served as the intervention. Measurements: Functional status was assessed using the Fibromyalgia Impact Questionnaire Revised (FIQR). Depression was evaluated with the Center for Epidemiologic Study of Depression (CES-D) measure. Measures were administered prior to participation in the program and approximately 5 months following completion of the program. Results: The cohort had a high prevalence of depressive symptoms (73.2% had depression at admission). Higher depression scores at baseline predicted poorer outcomes following multi-component treatment. Effectively treated depression resulted in improved functioning at follow-up. Limitations: Findings limited to tertiary care center cohort of fibromyalgia patients. Patients did not undergo a structured clinical diagnostic interview to diagnose depression. Conclusions: The current data links depression to poorer outcomes in patients with fibromyalgia. Depression is an important modifiable factor in the management of fibromyalgia. Guidelines should reflect the importance of assessing and effectively treating depression at the time of diagnosis of fibromyalgia, to improve functional outcomes. Registration: Specific registry and specific study registration number—Institutional Review Board—(IRB# 19-000495). Funding Source: No funding.